2002
DOI: 10.1002/jbm.10256
|View full text |Cite
|
Sign up to set email alerts
|

Model of the mechanism of Ca loss by bones under microgravity and earth conditions

Abstract: A comparative characterization of crystal structure, morphology, sizes, and orientation in Ca phosphate precipitation from aqueous solutions, the mineral phase in bones, and mineral deposits on cardiac valves has been performed by high-resolution transmission electron microscopy to model possible mechanisms of Ca loss by bones. Physiological changes occurring in organisms can lead to deep perturbations of the natural calcium phosphate supersaturation and its local distribution, which in turn influences the pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Two-dimensional nanocrystalline HA may be also synthesized [250]. Space-grown and terrestrial HA crystals were found to differ in size: the former appeared to be at least 1 – 1.5 orders of magnitude bigger in length [251,252]. Transparent HA ceramics can be prepared as well [253,254,255,256].…”
Section: The Members Of the Calcium Orthophosphate Familymentioning
confidence: 99%
“…Two-dimensional nanocrystalline HA may be also synthesized [250]. Space-grown and terrestrial HA crystals were found to differ in size: the former appeared to be at least 1 – 1.5 orders of magnitude bigger in length [251,252]. Transparent HA ceramics can be prepared as well [253,254,255,256].…”
Section: The Members Of the Calcium Orthophosphate Familymentioning
confidence: 99%
“…To our knowledge these conditions for the sample treatment are optimal and allowed to keep all possible Ca phosphate crystals and to fix an organic part unchanged (Elliot, 1994;Suvorova et al ., 2002;Suvorova et al ., 2004). Both uncoated and gold coated broken bone fragments were characterized by SEM and energy dispersive spectroscopy EDS in a FEI XL30 FEG microscope where the secondary electron SEM images were obtained at 1-10 kV accelerating voltage.…”
Section: Methodsmentioning
confidence: 98%
“…The present work is linked to our previous comprehensive structural investigation of hydroxyapatite (HAP) (Suvorova and Buffat, 2001a;Suvorova and Buffat, 2001b;Suvorova and Buffat, 2002;Suvorova et al ., 2004;Suvorova and Buffat, 2005) precipitated from aqueous solutions under different conditions and formed in living organisms (bones and cardiac valve deposition). A few years ago, a study compared the structure, morphology, and crystal size of Ca phosphate precipitated from aqueous solution and the mineral phase of bones and deposits on cardiac valves using TEM/HRTEM.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…9-432) and all peaks correspond to the hexagonal crystal form of HAp. 1,10,17,33,[47][48][49][50] From Figure 7, it can be seen that a decreasing degree of crystallinity leads to a decrease in intensity and an increase in width of the diffraction peaks. Moreover, the relative intensity of the peak (300) grows with the increase in the crystallinity degree, which shows that HAp may be oriented along the c-axis.…”
Section: The Fraction Of the Crystalline Phase In Hap Nanoparticlesmentioning
confidence: 99%